ChemInform Abstract: Persulfate‐Enabled Direct C—H Alkylation of Heteroarenes with Unactivated Ethers. Issue 43 (7th October 2016) - McCallum, Terry; Jouanno, Laurie‐Anne; Cannillo, Alexandre; Barriault, Louis
Abstract: A thermolytic potassium peroxodisulfate promoted oxidative C—H coupling of a range of N‐heterocycles with unactivated cyclic and non‐cyclic ethers is developed.